Modification of structural and magnetic properties of masked Co-Pt films induced by high-energy ion implantation - Kumar, Durgesh (2020)
Magnetic and structural properties of Co80Pt20 films were modified by controlled ion implantation through a dot-patterned mask for possible application in the mass production of patterned recording media. The dot patterns were fabricated using self-assembly of di-block copolymers. The effects of 14N+ and 40Ar+ ion implantation at energies as high as 40 and 100 keV, respectively, were studied. Although both ions cause changes in the structural and magnetic properties, 40 Ar+ ion implantation leads to more significant changes. The structural changes, predicted using simulations and experimentally observed using X-ray diffraction, indicate a mixing of Co into the layers below, leading to layers richer in Pt at the top. Magnetic force microscopy measurements show an increase in domain width and domain wall thickness as a function of ion fluences. The results are analyzed with measurements of magnetic anisotropy constant and micromagnetic simulations.